Le CLAS : un accompagnement à la scolarité ou une autre classe ? - Laurent Lescouarch; Marie Vergnon (Éducation et Socialisation)
Schooling support has become an important concern in the contemporary reshuffle of educational amenities, targeting some complementarity between school actions and extracurricular actions. This article, on the basis of an enquiry about a local contract for schooling support focusing its actions on homework assistance, highlights its characteristics as a protraction of school time and questions learning support ways and means in such amenities as regards in respect of their original aims developed in the 2001 schooling support charter.